A Case of Lichen Sclerosus et Atrophicus With Distinct Erythematous Borders. Issue 6 (November 2015) - Surkan, Megan; Hull, Peter
Background: Lichen sclerosus et atrophicus (LSA) is a chronic inflammatory and fibrosing condition that mostly affects the genital mucosa. Nongenital skin may be affected either in isolation or in association with genital involvement. A distinct, brightly red border may be seen but is poorly documented in major dermatology texts. In the case presented, such a border was noted in all of the patient's very extensive lesions. Objective: To draw attention to this clinical manifestation and to stimulate future observations as to its clinical and prognostic significance. Methods and Results: A 67-year-old woman presented with disseminated LSA with genital involvement. All the lesions had a distinct red border. A review of major textbooks available to the authors revealed that the presence of a marginal erythema is regularly not mentioned. Conclusion: An erythematous border to LSA may be a notable feature. Its frequency and clinical significance remain to be determined.